Liberdade e moral no pensamento de Jean-Paul Sartre - Mendes, Sheylla da Silva (2023)
The theme of freedom is inserted within Sartre's ontology, which is the founding basis of his philosophy of existence. In it we find the foundations of his doctrine and, consequently, of his investigation into the meaning assumed by human existence within his work. By dealing with the meaning and importance of his ontology, we also intend in this work to indicate the outline of his philosophical path and his insistent affirmation of freedom as a fundamental primacy and basic characteristic of the human condition. Therefore, this thesis is intended to address the possibilities, limits and crossroads of existentialist morality, giving special emphasis to the criticisms of its opponents and also to the innumerable difficulties that Sartrean philosophy faces when postulating a morality associated with the idea of freedom absolute. In this part, we intend to confirm the hypothesis that we will develop in this work according to which the moral proposed by Sartre proves to be insufficient to guide the subject's conduct and its impossibility occurs precisely because such a postulate would make his notion of absolute freedom inconsistent. In other words, we consider that the "Sartrean morality", by dispensing with a foundation or rules and prescriptions, proves to be incapable of offering a normative guideline for the subject's conduct. This means that such a proposal proves to be insufficient because the postulate of an existentialist morality would make its Sartrean notion of absolute freedom inconsistent.